DEVELOPMENT OF FARMER HOUSEHOLD FOOD SECURITY IN LAND MOVEMENT RAW AREAS IN KAWUNGLANCAR VILLAGE, NANGTANG VILLAGE, CIGALONTANG DISTRICT - Vepi Apiati; Mega Nur Prabawati; Siska Ryane Muslim; Aep Sunendar (Universitas Pamulang, 2021)
Nantang Village is an area that is prone to movement of the land, and is a hilly area. The location of soil movement occurs mostly in plantation areas which are located on hillside, has a low level of soil stability and can cause soil movement if there is a change of plants from strong and deep roots to small-rooted plants. To be able to overcome soil movements that can cause landslides, jackfruit seedlings are planted in areas prone to soil movement. The development of farmer household food security is carried out by training and counseling on planting vegetables in polybags and raising catfish in buckets which are expected to ensure adequate, safe, quality, nutritious food availability and food consumption, and close to the community itself. Community Service Activities Food Security Schemes (PbM-KP) can provide benefits and conveniences for the community in meeting their daily needs to get vegetables and fish.